Voting Patterns and the Gender Wage Gap - Wifag Adnan; Sami H. Miaari (Institute of Labor Economics (IZA), 2018)
Striving for gender equality presents major challenges but the benefits are vast, ranging from reduced conflict, both within and between communities, to higher economic growth. Unfortunately, Israel's gender wage gap remains one of the highest among developed countries, despite a growing reverse gender gap in educational attainment. Investigating the gender wage gap for the Jewish majority and for the Arab minority, we find evidence of gender segregation by industry and occupations in addition to a glass ceiling effect for Jewish and Arab women. Using data from the Israeli Household Income Survey and electoral data from the Israeli parliamentary elections (2009), this paper provides novel evidence of the role of voter preferences in explaining the persistence of gender pay gaps. Importantly, we find strong evidence of an association between a higher share of votes allocated to nationalist parties, in a given locality, and a larger, (adjusted), gender wage gap for both Jewish-Israelis and Arab-Israelis.
Keywords: J21; J31; J61; J45; C14; C24; 330; gender wage gap; voting behavior; glass ceiling; glass door; social attitudes; discrimination